2015
DOI: 10.1002/we.1869
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on wind turbine resonant vibrations

Abstract: Wind turbine resonant vibrations are investigated based on aeroelastic simulations both in frequency and time domain. The investigation focuses on three different aspects: the need of a precise modeling when a wind turbine is operating close to resonant conditions; the importance of estimating wind turbine loads also at low turbulence intensity wind conditions to identify the presence of resonances; and the wind turbine response because of external excitations. In the first analysis, three different wind turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Dynamic deflections of the main frame, potentially inducing undesirable loads on the drive train, have to be minimized. Resonance phenomena have a large impact on the loads and power efficiency of a wind turbine, see previous studies …”
Section: Introductionmentioning
confidence: 94%
“…Dynamic deflections of the main frame, potentially inducing undesirable loads on the drive train, have to be minimized. Resonance phenomena have a large impact on the loads and power efficiency of a wind turbine, see previous studies …”
Section: Introductionmentioning
confidence: 94%
“…Dimensioning of the monopiles is usually dictated by the fatigue loads, caused by wind and waves exciting primarily a combination of the two lowest tower modes, the fore‐aft mode in the rotor direction and the side‐side mode lateral to the rotor direction. Waves acting with an angle to the wind can therefore cause large fatigue damage because of the absence of the aerodynamic damping in the direction lateral to the wind . The future will see an increasing number of larger and more slender wind turbines positioned at deeper water depths .…”
Section: Introductionmentioning
confidence: 99%
“…Waves acting with an angle to the wind can therefore cause large fatigue damage because of the absence of the aerodynamic damping in the direction lateral to the wind. [1][2][3] The future will see an increasing number of larger and more slender wind turbines positioned at deeper water depths. 4 For these structures, the natural frequencies of the critical tower modes will be lower than for present day wind turbine structures, which will cause fatigue damage because of resonant wave loading to increase significantly.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of some trailing‐edge noise prediction models may be found in the work of Kamruzzaman et al On the other hand, outdoor noise emissions from isolated wind turbines and farms have been predicted from propagation models based on ray tracing that simulates the ground and air effects . In addition, the effect of resonant conditions in modern large‐scale wind turbines has recently been studied by Tibaldi et al , who reported that aeroelastic modes might be excited, depending upon the wind turbine operational external excitations.…”
Section: Introductionmentioning
confidence: 99%